2011
DOI: 10.1596/1813-9450-5615
|View full text |Cite
|
Sign up to set email alerts
|

Too little too late: Welfare impacts of rainfall shocks in rural Indonesia

Abstract: We consider two shocks: (i) a delay in the onset of monsoon and (ii) a significant shortfall in rainfall in the 90 day post-onset period. Focusing on households with family farm businesses, we find that a delay in the monsoon onset does not have a significant impact on the welfare of rice farmers. However, rice farm households located in areas exposed to low rainfall following the monsoon are negatively affected. Rice farm households appear to be able to protect their food expenditure in the face of weather sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…The positive effect of education on consumption was also reported in studies investigating consumption smoothing at the household level. Studies in rural Malawi and in Indonesia reported higher per capita consumption among households with heads who had higher education levels (Davies 2010, Skoufias et al 2011. Education is positively associated with recovery after natural disasters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effect of education on consumption was also reported in studies investigating consumption smoothing at the household level. Studies in rural Malawi and in Indonesia reported higher per capita consumption among households with heads who had higher education levels (Davies 2010, Skoufias et al 2011. Education is positively associated with recovery after natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, upon seeing that natural disasters can reduce the expected return to physical capital, rational individuals may shift their investment toward human capital (Skidmore and Toya 2002). Because there is evidence that households adjust their consumption in response to an adverse shock differentially, e.g., reducing nonfood consumption but smoothing food consumption (Skoufias et al 2011), it is important to analyze the impacts of catastrophic climate shocks on the different dimensions of welfare. We used five variables as indicators of welfare, namely, food expenditure, nonfood expenditure, productive expenditure on agriculture, expenditure on education, and income.…”
Section: Methodsmentioning
confidence: 99%
“…Rural areas are characterised by high dependence on agriculture, low human development levels, low adaptive capacities and receive little attention from policymakers (Skoufias et al 2011;Dasgupta et al 2014;Panthi et al 2015). According to the IPCC Fifth Assessment Report (Dasgupta et al 2014), climate change introduces grave implications for rural areas through a direct toll on rural livelihoods.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with at least one other study from Indonesia that documented the effects of early-life rainfall levels on later-life health outcomes (Maccini and Yang 2009). However, other research suggests that delays in monsoon onset have a particularly strong and significant impact on rice and maize production, which plays a key role in the Indonesian economy (Naylor et al 2002(Naylor et al , 2007 and has important consequences for household economic status (Skoufias et al 2012). These findings suggest that the timing of the monsoon has effects on rice production and local economies that are independent of total rainfall.…”
Section: Current Studymentioning
confidence: 99%
“…We apply this approach to mean temperature, total rainfall, and monsoon onset delay. Building on previous studies of Indonesia, monsoon onset is defined as the number of days after August 1 that pass until cumulative rainfall reaches 20 cm (Naylor et al 2007;Skoufias et al 2012). Our analyses of household income utilize similar measures of temperature and monsoon onset delay, but only over the one-year periods for which income was measured (see below).…”
Section: Climate Measuresmentioning
confidence: 99%